Adipocyte Versus Somatotrope Leptin: Regulation of Metabolic Functions in the Mouse - Odle, Angela Katherine (Endocrinology, 2016)
Leptin regulates food intake and energy expenditure (EE) and is produced in adipocytes, the pituitary, and several other tissues. Animals that are leptin or leptin receptor deficient have major metabolic complications, including obesity. This study tests the hypothesis that the pituitary somatotrope may contribute a source of leptin that maintains some of these metabolic functions. We created 2 different tissue-specific leptin knockout animals: a Somatotrope-Lep-null model and an Adipocyte-Lep-null model. Metabolic analysis of both models, along with a global deletion model, was performed. The Somatotrope-Lep-null animals had fewer somatotropes, and females had a 76% decrease in serum prolactin. During the dark (feeding) phase, females had a 35% increase in ambulation coupled with a 4% increase in EE. Mutants showed no change in food intake or weight gain and EE was unchanged in males. During the light (sleep) phase, Somatotrope-Lep-null mutant males had lower EE and females continued to have higher EE. The respiratory quotients (RQs) of mutants and littermate controls were decreased in males and increased in females; all were within the range that indicates predominant carbohydrate burning. The massively obese Adipocyte-Lep-null animals, however, had significant increases in food intake, sleep, and increased EE, with decreased activity. Changes in RQ were sexually dimorphic, with female mutants having higher RQ and males having decreased RQ. We conclude that both adipocyte and somatotrope leptin contribute to the metabolic homeostasis of the mouse, and that extraadipocyte sources of leptin cannot overcome the major metabolic challenges seen in these animals.